Finite-time output tracking control for air-breathing hypersonic vehicles with actuator constraints. (December 2017) - An, H; Xia, H; Wang, C
This paper designs a finite-time output tracking controller for air-breathing hypersonic vehicles (AHVs) subjected to disturbances and actuator constraints. After proper derivations, the original model is divided into two independent subsystems undergoing mismatched lumped disturbance. A finite-time disturbance observer (FTDO) is employed to estimate the lumped disturbance, while an auxiliary system combined with a command pre-filter is designed to analyze the effect of input saturation caused by the restrained actuators. Based on the FTDO and the auxiliary system, a novel integral sliding surface is constructed and then a chattering-free nonsingular controller is developed to realize finite-time output tracking in spite of mismatched lumped disturbance and input saturation, which is its major merit compared with other existing AHV controllers. A simulation study is carried out to verify the proposed control scheme.